Green infrastructure in arid urban contexts. Transitioning ecologies beyond Green Riyadh - Monica Moscatelli; Alessandro Raffa (Agathón)
Green infrastructures play a crucial role in urban transitions by integrating and coordinating the environmental, economic, and social dimensions. This contribution focuses on green infrastructures within urban contexts characterised by an arid climate, particularly in Riyadh as a hologram of the Saudi city. The goal is to outline the current role of green infrastructure between plans and projects, identifying future limits and possibilities through a ‘landscape-based’ approach to green infrastructure. Seven integrated and interacting strategic lines will therefore be identified, which aim to inform the process of implementation of the green infrastructure in a holistic and complex key, opening up to alternative scenarios of ecological transition for the Saudi city.